In Silico Study of Quercetin and Its Derivatives as Potential Antituberculosis - Angelina Stevany Regina Masengi; Greachylia Chelzy; Jimmy Posangi; Trina Ekawati Tallei; Fatimawali; Christi Diana Mambo; Dian Augina Rintibulawan Rambulangi (JURNAL BIOS LOGOS, 2025)
Tuberculosis (TB) remains the second leading cause of death in the world, with the resistance of Mycobacterium tuberculosis to first-line drugs, such as isoniazid (INH), contributing to the emergence of multi-drug resistant TB (MDR-TB). This study aims to evaluate the potential of quercetin and its derivatives as InhA enzyme inhibitors through an in silico approach to offer innovative therapeutic alternatives to improve the effectiveness of TB treatment. The analysis includes physicochemical properties, ADMET profiles, molecular interactions, and affinity of compounds to the InhA enzyme as an antituberculosis target. The study workflow included ligand and receptor preparation, prediction of biological activity, physicochemical and ADMET analysis, docking validation, molecular docking, and visualization of molecular interactions. Molecular docking was performed using Gnina software, showing that rutin has the lowest binding energy (ΔG) of -12.22 kcal/mol, indicating strong interaction affinity. In addition, ADMET and toxicity analysis showed good pharmacokinetic potential for the test compounds Docking validation confirmed the reliability of the employed methodology, further supporting the potential of quercetin and its derivatives as antituberculosis candidates. However, although quercetin and its derivatives showed promising biological activity, the ADMET profile results were variable, requiring further optimization to develop effective and safe TB therapies.